(3Ohd GdESdGes - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s; (3GdPgHj,J (B748 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdYdj GdcHjQ Ydi GdMeO dg , aEfg fYe Gdhdj hfYe GdfUjQ, CMeOg Ydi eG ef YdjfG HGdESdGe , hdRhe GdSfI hGdLeGYI s
(3BNQgG (B:s
(3aj PcQ hajGJ SfI CQHY hCQHYjf hSHYeGFI , hgh BNQ GdcJGH s
(3GfXQ CjkVG Qbe (B662s
(3Qbe (B1047 (3JGQjNs
(3GdfSNI HgG MhGTs
(3fSNI NGeSI Ydi ghGeTgG JbjjOGJ HgG UaMJGf jTJedGf Ydi HYV GdhajGJ s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3GdJGQjNs